Improving The Students’ Speaking Ability In Giving Suggestions And Advice By The Use Of "Whip Around" Strategy In The Second Grade Of SMA Negeri 8 Medan - Zalukhu, Atalisi; Hulu, Mey Trisnawati; Giawa, Kardelius; Manik, Sondang; Manurung, Lastri Wahyuni (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Speaking is the ability to convey information or expressing to convey everything in their mind orally. Therefore, it is important for students to master speaking in their daily life because through speaking students can express their ideas, feelings, opinions, and knowledge. There were some problems faced by the students in speaking in Second grade of SMA Negeri 8 Medan namely: the students lacked vocabularies, and the students are not able to deliver their suggestion and advice. Therefore, to overcome the problems, the researcher conducted this research by using “Whip Around” Strategy in second grade of SMA Negeri 8 Medan. The purpose of the research is to Improving the students’ ability in speaking by using whip around Strategy at the second grade of SMA Negeri 8 Medan. To achieve the purpose, the researcher conducted CAR Method. The result of the data in Cycle I showed the average of students’ value was 60, the maximum score was 78 and the minimum score was 41. While in Cycle II 20 students (100%), the student got the maximum score was 83 and the minimum score was 75. From the result o the research, it can be concluded that “Whip Around” Strategy Improvings the students’ speaking ability in second grade of SMA Negeri 8 Medan. Finally, the researcher suggested all English teacher to use this strategy in teaching speaking skill because “Whip Around” Strategy is effective to Improving the students’ ability in speaking. “Whip Around” Strategy encourages the students’ to express their suggestion and advice orally and engaged the student high motivation during the teaching and learning process. Keywords: Speaking Ability; Suggestion; Advice; Whip Around Strategy. Abstrak Berbicara adalah kemampuan untuk menyampaikan informasi atau mengungkapkan untuk menyampaikan segala sesuatu dalam pikiran mereka secara lisan. Oleh karena itu, penting bagi siswa untuk menguasai berbicara dalam kehidupan sehari-hari karena melalui berbicara siswa dapat mengungkapkan ide, perasaan, pendapat, dan pengetahuannya. Ada beberapa masalah yang dihadapi siswa dalam berbicara di kelas II SMA Negeri 8 Medan yaitu: siswa kekurangan kosa kata, dan siswa tidak mampu menyampaikan saran dan nasihat mereka. Oleh karena itu, untuk mengatasi masalah tersebut, peneliti melakukan penelitian ini dengan menggunakan Strategi “Whip Around” di kelas II SMA Negeri 8 Medan. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan siswa dalam berbicara dengan menggunakan strategi cambuk di kelas dua SMA Negeri 8 Medan. Untuk mencapai tujuan tersebut, peneliti melakukan Metode PTK. Hasil data pada Siklus I menunjukkan rata-rata nilai siswa 60, nilai maksimal 78 dan nilai minimal 41. Sedangkan pada Siklus II 20 siswa (100%), siswa mendapat nilai maksimal 83 dan skor minimal adalah 75. Dari hasil penelitian, dapat disimpulkan bahwa Strategi “Whip Around” meningkatkan kemampuan berbicara siswa di kelas dua SMA Negeri 8 Medan. Akhirnya, peneliti menyarankan semua guru bahasa Inggris untuk menggunakan strategi ini dalam mengajar keterampilan berbicara karena Strategi “Whip Around” efektif untuk meningkatkan kemampuan siswa dalam berbicara. Strategi “Whip Around” mendorong siswa untuk mengungkapkan saran dan nasihat mereka secara lisan dan melibatkan motivasi siswa yang tinggi selama proses belajar mengajar. Kata Kunci: Kemampuan Berbicara; Saran; Nasihat; Cambuk Sekitar Strategi.